2010
DOI: 10.1021/ac102806p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Differences between Blood Sample Matrices in Untargeted Metabolomics

Abstract: Large-scale proteomic and metabolomic technologies are increasingly gaining attention for their use in the diagnosis of human disease. In order to ensure the statistical power of relevant markers, such analyses must incorporate a large number of representative samples. While in a best-case scenario these samples are collected through a study design that is specifically tailored for the desired analysis, often studies must rely upon the analysis of large numbers of previously banked samples that may or may not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 48 publications
3
79
0
Order By: Relevance
“…This analysis resulted in the extraction of 7,343 features from the LC-MS data of mouse sera samples. The number of features detected in our analysis are comparable to other plasma and serum metabolomics studies using this methodology (Denery et al 2011, Dunn et al 2011. Unsupervised PCA score plots that show the first (PC1) and second (PC2) components for three pair-wise comparisons (Y-AL vs. A-AL, A-AL vs. A-CR, and Y-AL vs. A-CR) are presented in Fig.…”
Section: Global Metabolomics Analysissupporting
confidence: 77%
“…This analysis resulted in the extraction of 7,343 features from the LC-MS data of mouse sera samples. The number of features detected in our analysis are comparable to other plasma and serum metabolomics studies using this methodology (Denery et al 2011, Dunn et al 2011. Unsupervised PCA score plots that show the first (PC1) and second (PC2) components for three pair-wise comparisons (Y-AL vs. A-AL, A-AL vs. A-CR, and Y-AL vs. A-CR) are presented in Fig.…”
Section: Global Metabolomics Analysissupporting
confidence: 77%
“…But is serum also appropriate for metabolomics studies? A targeted and a nontargeted metabolomics study reported an acceptable correlation of the metabolic pattern between serum and plasma (16,17 ). However, in serum the concentrations of 104 of 121 metabolites were higher (around 10%), and 9 metabolites associated with the clotting process during serum generation showed obvious differences (20%-50%) (16 ).…”
Section: Fig 4 Impact Of Placing Freshly Drawn Blood In Ice Water Fmentioning
confidence: 98%
“…Selected preanalytical aspects of targeted metabolomics investigations of human blood and urine by GC-MS and LC-MS (11)(12)(13)(14)(15)(16)(17), as well as the effects of delayed storage on human cerebrospinal fluid metabolomes (18 ), have been reported. Recently, protocols for metabolic profiling of serum and plasma have been published (3,7,19 ).…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
“…For instance, lysophosphatidylinositol has been implicated in cancer, but recent reports show that levels of this compound are very sensitive to the activation or inactivation of the blood-clotting cascade, thus necessitating stringent sample-preparation procedures (time to processing, temperature of processing) to avoid artifacts [48]. This study suggests that tentative role of lysophosphatidylinositol as a potential biomarker of cancer must be examined to ensure the analytical approach was sufficient to detect true changes in this metabolite and does not reflect differences in preanalytical handling of the collected blood samples.…”
Section: Importance Of Sample Preparation In Global Metabolomicsmentioning
confidence: 99%